PEMENUHAN KEBUTUHAN AIR BERSIH MASYARAKAT KEPULAUAN SERIBU MELALUI OPTIMASI PEMANFAATAN PENAMPUNG AIR HUJAN - Rahardjo, Petrus Nugro (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2000)
The very limited natural resources, especially in small islands such as in Thousand Island, north Jakarta, may cause a lot of environmental problems if the inhabitant is not wise in managing and exploiting its environmental power resources. One of the chronic problems in Thousand Island is the lack of clean water availability. That specific problem becomes worse and worse because of increasing of the population. In dry season the condition always gets worst. Many acts have been done to deal with the problem, but in fact until now it can not be solved properly. After doing a direct survey to all densely populated islands in Thousand island, it is found that one good alternative can possibly be done to solve the problem. It is to develop and maximize the using of rain water reservoir (PAH). Based on the calculation using two approaches, the fact that rain water reservoir in Untung Jawaand Lancang Besar island are already enough. For Tidung Besar, Panggang and Pramuka island, they need to enlarge the roof as a receiver of rain-water falling down. Another alternatif that should be carried out is to rehabilitate all the damage rain-water reservoirs. Kelapa island needs not only roof enlarging and rehabilitation of the rain-water reservoirs, but also developing some new rain-water reservoirs. Harapan island still needs developing some new rain-water reservoirs and roof enlarging to get more rain water.